IMPROVING THE MECHANISM OF STATE REGULATION OF INNOVATION ACTIVITIES IN TURKESTAN REGION - Kokеnova, A.E.; Maulenkulovа, G.E.; Samenova, N.Zh.; Turdalieva, U.N.; Arapbaeva, Zh.Sh. (Scientific Journal of Pedagogy and Economics, 2020)
The importance of innovation in ensuring the development of a modern economy has been recognized in Kazakhstan not only in the works of specialists, but also in the position stated by the state. However, from understanding the importance of innovation in the context of economic development to understanding its real significance in the economic development of the country, and even more so - to develop an effective policy that ensures the active use of innovation to ensure economic and social progress, a very difficult path runs. Regulation of innovation in a modern market economy is a complex system of state, public and corporate institutions that serve and regulate innovation processes in order to ensure the fullest use of their potential. A set of institutions and organizations that cover all stages and areas of the innovation process, and currently forms a national innovation system in developed market economies. The trend of transition to an innovative way of development and the formation of a national innovation system is currently an important direction in economic science. This makes it particularly important to theoretically understand the essence of the innovation process in the economy and ways to improve the effectiveness of state regulation of innovation. Thus, the development of a mechanism for activating innovation activities within the framework of the state regulation system is one of the most acute socio-economic problems. The obvious relevance, great practical significance and lack of development of the indicated problem led to the choice of the topic of the dissertation research, its goals and objectives. In the scientific article, the conditions for effective innovation activity of economic entities are identified and based on them, recommendations are developed to improve the mechanism for increasing innovation activity within the system of state regulation of innovation activity of the Kazakh economy.